Mapping the global health burden of volcanic exposure: a scoping review approach - Simbaña-Rivera, Katherine; Endara-Mina, Jesús; Jaramillo-Aguilar, Damary S.; Mera-Lojano, Leonardo D.; Jimbo-Sotomayor, Ruth; Sánchez, Xavier; Rodríguez-Pérez, María Cristo; Fuentes-Ferrer, Manuel Enrique; Boada, Luis D. (Frontiers in Public Health, 2025)
BackgroundVolcanic eruptions pose substantial health risks to populations living in proximity to active volcanoes, impacting respiratory, cardiovascular, ocular, dermatological, and mental health systems. With a growing number of people globally exposed to volcanic activity, there is a critical need for an interdisciplinary understanding of these health consequences, particularly concerning their pathophysiological mechanisms, epidemiological patterns, and public health implications.MethodsThis scoping review systematically synthesized evidence from studies conducted near 27 volcanoes across diverse geographic regions. The analysis integrated clinical, epidemiological, and public health perspectives to characterize health outcomes and associated risk factors, including geographic location, eruption magnitude, and type of exposure. A novel schematic framework was developed to map pathophysiological mechanisms across multiple organ systems.FindingsThe results indicate that volcanic emissions—such as sulphur dioxide, fine tephra, and volcanic ash—exacerbate pre-existing conditions and contribute to increased morbidity. The most frequently reported health outcomes included acute respiratory symptoms, conjunctivitis, dermatitis, hypertension, and post-traumatic stress disorder. Variability in health impacts was observed across sex, age, and region, with vulnerable groups such as children and older adults disproportionately affected. Chronic exposure was associated with persistent health issues, revealing critical gaps in long-term health surveillance and intervention strategies.ConclusionThis scoping review highlights the multifaceted health impacts of volcanic eruptions, emphasizing the complex interactions between volcanic emissions and human health. The findings underscore the need for tailored public health interventions, proactive education, and further research to strengthen preparedness and resilience in exposed communities.